Transcriptome Analysis Identifies a Zinc Finger Protein Regulating Starch Degradation in Kiwifruit. Issue 2 (22nd August 2018) - Zhang, Ai-di; Wang, Wen-qiu; Tong, Yang; Li, Ming-jun; Grierson, Donald; Ferguson, Ian; Chen, Kun-song; Yin, Xue-ren
Abstract : An ethylene responsive C2H2-type zinc finger transcription factor, AdDof3, regulates starch degradation in kiwifruit via trans-activation of the AdBAM3L promoter. Abstract: Ripening, including softening, is a critical factor in determining the postharvest shelf-life of fruit and is controlled by enzymes involved in cell wall metabolism, starch degradation, and hormone metabolism. Here, we used a transcriptomics-based approach to identify transcriptional regulatory components associated with texture, ethylene, and starch degradation in ripening kiwifruit ( Actinidia deliciosa ). Twelve differentially expressed structural genes, including seven involved in cell wall metabolism, four in ethylene biosynthesis, and one in starch degradation, and 14 transcription factors (TFs) induced by exogenous ethylene treatment and inhibited by the ethylene signaling inhibitor 1-methylcyclopropene were identified as changing in transcript levels during ripening. Moreover, analysis of the regulatory effects of differentially expressed genes identified a zinc finger TF, DNA BINDING WITH ONE FINGER (AdDof3), which showed significant transactivation on the AdBAM3L (β-amylase) promoter. AdDof3 interacted physically with the AdBAM3L promoter, and stable overexpression of AdBAM3L resulted in lower starch content in transgenic kiwifruit leaves, suggesting that AdBAM3L is a key gene for starch degradation. Moreover, transient overexpression analysis showed that AdDof3 up-regulated AdBAM3L expression in kiwifruit. Thus, transcriptomics analysis not only allowed the prediction of some ripening-regulating genes but also facilitated the characterization of a TF, AdDof3, and a key structural gene, AdBAM3L, in starch degradation.